Effects of managerial leadership power bases on employees' job commitment in the nationalised commercial banks of Bangladesh - Jahangir, Nadim; Haq, Mahmudul (© 2005 Bank Parikrama, 2017)
This article was published in the Bank Parikrama (A Journal of Banking & Finance) [ @ 2005 Bank Parikrama. ]